C:N:P proportions in nutrients, particulate organic matter and dissolved organic matter from surface to maximum up to 2000 m water depth in the Bay of Bengal (Indian Ocean) during spring 2019 - Deepika Sahoo; Himanshu Saxena; Sipai Nazirahmed; Sanjeev Kumar; A K Sudheer; Ravi Bhushan; Arvind Sahay; Arvind Singh (PANGAEA, 2021)
The data present the carbon, nitrogen, and phosphorus content and their ratios (C:N, N:P, C:P) in the dissolved inorganic nutrient, particulate organic matter, and dissolved organic matter pools from 5 m to a maximum of 2000 m depth in the Bay of Bengal during spring (5 April to 15 April 2019) in ORV Sindhu Sankalp expedition (SSK 127). The seawater samples were collected using a Sea-Bird CTD rosette sampler at a maximum of 10 different depths (5, 25, 50, 85, 200, 300, 500, 1000, 1500, and 2000 m). The columns in the dataset include the date of sampling, latitude, longitude, depth, DIC (dissolved inorganic carbon), DIN (dissolved inorganic nitrogen (nitrate + nitrite)), DIP (dissolved inorganic phosphorus (phosphate)), POC (particulate organic carbon), PON (particulate organic nitrogen), POP (particulate organic phosphorus), DOC (dissolved organic carbon), DON (dissolved organic nitrogen), DOP (dissolved organic phosphorus), δ13C of DIC, and elemental ratios including DIC:DIN, DIN:DIP, DIC:DIP, POC:PON, PON:POP, POC:POP, DOC:DON, DON:DOP, and DOC:DOP. DIC was measured using Coulometer (UIC extquotesingles Model 5012, USA) with an analytical precision of ± 2%. δ13C values of DIC were measured using GasBench II attached to an Isotope Ratio Mass Spectrometer (Thermo Scientific MAT 253) with a precision better than 0.10 %. Nutrients such as DIN and DIP were measured using an autoanalyzer (SKALAR, The Netherlands). Reliability of the nutrients data was obtained daily by measuring certified reference material: MOOS-3 from National Research Council, Canada. POC and PON concentrations were measured using an Elemental Analyzer (FLASH 2000; Thermo Scientific) coupled with an Isotope Ratio Mass Spectrometer (Delta V Plus; Thermo Scientific) connected via conflo interface. The analytical precision for both POC and PON measurements were <10%. Total phosphorus (TP) and POP were measured by using high-temperature oxidation method. Samples (seawater for TP and filtered samples on GF/F for POP) were digested at 15 psi for 80 min in an autoclave, followed by their analysis in Shimadzu Spectrophotometer (UV-1800, Japan). The detection limit of the measurements was 0.1 nM. Total organic carbon (TOC) measurements were performed using high temperature catalytic oxidation method in Shimadzu TOC analyzer (TOC-L-CPH, Japan) and total nitrogen (TN) measurements were performed in Shimadzu TN analyser (TNM-L-CPH, Japan). Total organic N (TON) and total organic P (TOP) were estimated by subtracting inorganic matter from its total elemental pool such as [TN]–[DIN] and [TP]–[DIP], respectively. Dissolved organic C (DOC), N (DON), and P (DOP) concentrations were quantified as the difference between TOC and POC, TON and PON and TOP and POP, respectively.